Teknik Pengawetan Fillet Ikan Nila Merah dengan Senyawa Anti Bakteri asal Lactobacillus Acidophilus dan Bifido Bacteria Biffidum - Saputra, Dede; Nurhayati, Tati (Bina Nusantara University, 2014)
Red tilapia is a good commodity to be developed because it has a high nutritional value composition, with a protein content 17.8%, fat 2.8%, and others composition. The fillet of red tilapia fish is easy to spoil, because of S. aureus, Salmonella sp., and other microbes. Many methods are used to save and preserve the quality of fillet, such fillet preparation through good sanitation practices, cooling process, but the effort were not optimal. The objectives of this study were to 1) evaluate the potency of antibacterial produced by Lactobacillus acidophilus and Bifidobacteria biffidum to inhibit the growth of spoilage bacteria that contaminated the red tilapia fillet; 2) evaluate the effect of antibacterial compounds produced by Lactobacillus acidophilus and Bifidobacteria biffidum of inhibiting the setback fillet quality, 3) determine the shelf life of red tilapia fillet at room temperature. Antibacterial activity test is done by using the well diffusion method; the rate of deterioration of quality of fish tests done by observing the organoleptic parameters, pH measurement test, total volatile base method. Total number of bacteria were performed by Standard Plate Count (SPC) test. The LAB’s are able to inhibit the growth of spoilage bacteria Pseudomonas aeruginosa about 8.67-9.00 mm and Listeria monocytogenes about 8.33-9.00 mm through the well diffusion method. pH values about 5.71-5.74, TVB values about 1,26-21.43 with SPC test about 1.39-4.83 CFU/mL. The antibacterial compounds could inhibit the rate of deterioration of quality red tilapia fillets until 14 hours.